Respuesta :
The Lagrangian is
[tex]L(x,y,z,\lambda)=x^2y^2z^2+\lambda(x^2+y^2+z^2-1)[/tex]
where we assume [tex]\lambda\neq0[/tex], with critical points wherever the partial derivatives are identically zero:
[tex]L_x=2xy^2z^2+2\lambda x=0\implies2x(y^2z^2+\lambda)=0\implies x=0\text{ or }y^2z^2=-\lambda[/tex]
(note that the latter case requires [tex]\lambda<0[/tex], and we'll see the same requirement in the next two equations)
[tex]L_y=2x^2yz^2+2\lambda y=0\implies2y(x^2z^2+\lambda)=0\implies y=0\text{ or }x^2z^2=-\lambda[/tex]
[tex]L_z=2x^2y^2z+2\lambda z=0\implies2z(x^2y^2+\lambda)=0\implies z=0\text{ or }x^2y^2=-\lambda[/tex]
[tex]L_\lambda=x^2+y^2+z^2-1=0[/tex]
If either [tex]x=0[/tex], [tex]y=0[/tex], or [tex]z=0[/tex], then we can throw out the latter cases for [tex]L_x=0[/tex], [tex]L_y=0[/tex], and [tex]L_z=0[/tex], since we don't want [tex]\lambda=0[/tex]. If, for instance, we pick [tex]x=y=0[/tex], then we're left with [tex]z^2=1\implies z=\pm1[/tex], for which [tex]f(x,y,z)=0[/tex]. This means we have 6 critical points [tex](x,y,z)[/tex] where two of the coordinates are 0, and the remaining one is either 1 or -1.
In the latter case,
[tex]y^2z^2=x^2z^2=-\lambda\implies x^2=y^2\implies x=\pm y[/tex]
[tex]x^2z^2=x^2y^2=-\lambda\implies z^2=y^2\implies y=\pm z[/tex]
[tex]y^2z^2=x^2y^2=-\lambda\implies x^2=z^2\implies z=\pm x[/tex]
If [tex]x=y=z[/tex], then
[tex]3x^2=1\implies x=y=z=\pm\dfrac1{\sqrt3}[/tex]
A similar thing happens in all the other cases, which leads us to getting 8 possible critical points, [tex]\left(\pm\dfrac1{\sqrt3},\pm\dfrac1{\sqrt3},\pm\dfrac1{\sqrt3}\right)[/tex]; at each of these points, we have [tex]f(x,y,z)=\dfrac1{27}[/tex].
To summarize: [tex]f(x,y,z)[/tex] has a maximum value of 1/27 and a minimum value of 0.
The extreme values of a function are the minimum and the maximum values of the function.
The minimum and the maximum values are 0 and 1/27, respectively.
The function is given as:
[tex]\mathbf{f(x,y,z) = x^2y^2z^2}[/tex]
[tex]\mathbf{x^2 + y^2 +z^2 = 1}[/tex]
Subtract 1 from both sides of [tex]\mathbf{x^2 + y^2 +z^2 = 1}[/tex]
[tex]\mathbf{x^2 + y^2 +z^2 -1= 0}[/tex]
Using Lagrange multiplies, we have:
[tex]\mathbf{L(x,y,z,\lambda) = f(x,y,z) + \lambda(0)}[/tex]
Substitute [tex]\mathbf{f(x,y,z) = x^2y^2z^2}[/tex] and [tex]\mathbf{x^2 + y^2 +z^2 -1= 0}[/tex]
[tex]\mathbf{L(x,y,\lambda) = x^2y^2z^2 + \lambda(x^2 + y^2 +z^2 - 1)}[/tex]
Differentiate
[tex]\mathbf{L_x = 2xy^2z^2 + 2\lambda x}[/tex]
[tex]\mathbf{L_y = 2x^2yz^2 + 2\lambda y}[/tex]
[tex]\mathbf{L_z = 2x^2y^2z + 2\lambda z}[/tex]
[tex]\mathbf{L_{\lambda} =x^2 + y^2 +z^2 -1}[/tex]
Equate to 0
[tex]\mathbf{2xy^2z^2 + 2\lambda x = 0}[/tex]
[tex]\mathbf{2x^2yz^2 + 2\lambda y = 0}[/tex]
[tex]\mathbf{2x^2y^2z + 2\lambda z = 0}[/tex]
[tex]\mathbf{x^2 + y^2 +z^2 -1= 0}[/tex]
Factorize the above expressions
[tex]\mathbf{2xy^2z^2 + 2\lambda x = 0}[/tex]
[tex]\mathbf{ 2x(y^2z^2 + \lambda) = 0}[/tex]
[tex]\mathbf{ 2x = 0\ or\ y^2z^2 + \lambda = 0}[/tex]
[tex]\mathbf{x = 0\ or\ y^2z^2 =- \lambda}[/tex]
[tex]\mathbf{2x^2yz^2 + 2\lambda y = 0}[/tex]
[tex]\mathbf{2y(x^2z^2 + \lambda) = 0}[/tex]
[tex]\mathbf{ 2y = 0\ or\ x^2z^2 + \lambda = 0}[/tex]
[tex]\mathbf{y = 0\ or\ x^2z^2 =- \lambda}[/tex]
[tex]\mathbf{2x^2y^2z + 2\lambda z = 0}[/tex]
[tex]\mathbf{2z(x^2y^2 + \lambda) = 0}[/tex]
[tex]\mathbf{2z= 0\ or\ x^2y^2 + \lambda = 0}[/tex]
[tex]\mathbf{z= 0\ or\ x^2y^2 =- \lambda }[/tex]
So, we have:
[tex]\mathbf{x = 0\ or\ y^2z^2 =- \lambda}[/tex]
[tex]\mathbf{y = 0\ or\ x^2z^2 =- \lambda}[/tex]
[tex]\mathbf{z= 0\ or\ x^2y^2 =- \lambda }[/tex]
Because
-λ = -λ
The above expressions become:
[tex]\mathbf{x = y = z = 0}[/tex]
[tex]\mathbf{x^2z^2 =y^2z^2 }[/tex]
[tex]\mathbf{x^2 = y^2}[/tex]
[tex]\mathbf{x = \pm y}[/tex]
Also, we have:
[tex]\mathbf{x^2y^2 =x^2z^2 }[/tex]
[tex]\mathbf{y^2 =z^2 }[/tex]
[tex]\mathbf{y =\pm z}[/tex]
Also:
[tex]\mathbf{y^2z^2 =x^2y^2}[/tex]
[tex]\mathbf{z^2 =x^2}[/tex]
[tex]\mathbf{z =\pm x}[/tex]
So, we have:
[tex]\mathbf{x = \pm y}[/tex]
[tex]\mathbf{y =\pm z}[/tex]
[tex]\mathbf{z =\pm x}[/tex]
This means that:
[tex]\mathbf{x = y = z}[/tex]
Recall that: [tex]\mathbf{x^2 + y^2 +z^2 = 1}[/tex]
So, we have:
[tex]\mathbf{x^2 + x^2 + x^2 = 1}[/tex]
[tex]\mathbf{3x^2 = 1}[/tex]
Divide through by 3
[tex]\mathbf{x^2 = \frac13}[/tex]
Take square roots of both sides
[tex]\mathbf{x = \pm \frac1{\sqrt3}}[/tex]
So, we have:
[tex]\mathbf{x =y = z= \pm \frac1{\sqrt3}}[/tex]
So, the critical points are:
[tex]\mathbf{x = y = z = 0}[/tex]
[tex]\mathbf{x =y = z= \pm \frac1{\sqrt3}}[/tex]
Substitute the above values in [tex]\mathbf{f(x,y,z) = x^2y^2z^2}[/tex]
[tex]\mathbf{f(0,0,0) = 0^2 \times 0^2 \times 0^2 = 0}[/tex]
[tex]\mathbf{f(\pm \frac1{\sqrt3},\pm \frac1{\sqrt3},\pm \frac1{\sqrt3}) = (\pm \frac1{\sqrt3})^2 \times (\pm \frac1{\sqrt3})^2 \times (\pm \frac1{\sqrt3})^2 = \frac{1}{27}}[/tex]
Considering the above values, we have:
[tex]\mathbf{Minimum= 0}[/tex]
[tex]\mathbf{Maximum= \frac{1}{27}}[/tex]
Hence, the minimum and the maximum values are 0 and 1/27, respectively.
Read more about extreme values at;
brainly.com/question/1286349